Book review Bats in the Anthropocene - Conservation of Bats in a Changing World. (Terr@ Plural, 2020)
Book Review Voigt, Christian C., and Tigga Kingston. Bats in the Anthropocene - Conservation of Bats in a Changing World. Springer Science+ Business Media, 2016, 601 pages. ISBN 978-3-319-25218-6 / ISBN 978-3-319-25220-9 (eBook). Price: free.
Keywords: Resenha; morcegos; Antropoceno